Was macht eigentlich ...? : 100 DDR-Prominente heute - Zimmermann, Monika 1949- Hrsg (Links, 1994)
Enth. u. a. Manfred von Ardenne , Rudolf Bahro , Arndt Bause , Ibrahim Böhme , Jurij Brezan , Kurt Drummer , Manfred Ewald , Irma Gabel - Thälmann , Erwin Geschonneck , Günter Görlich , Klaus Höpcke , Sigmund Jähn , Marita Koch , Egon Krenz , Lothar de Maiziere , Hans-Peter minetti , Margarete Müller , Dieter Noll , Oktoberklub , Hans-joachim Preil , Karl-Eduard von Schnitzler , wolfgang Schnur , Frank schöbel , Gustav Adolf Schur (Täve) , Hans-dieter Schütt , Willi Sitte , Erwin Strittmatter , Harald Wessel , Walter Womacka